2011
DOI: 10.1097/ta.0b013e3181febc8f
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Major Burn Disasters in Resource-Limited Settings: Lessons Learned From an Oil Tanker Explosion in Nakuru, Kenya

Abstract: Background: On January 31, 2009, a fuel tanker exploded in rural Kenya, killing and injuring hundreds of people. This article describes the care of Ͼ80 burn victims at a rural hospital in Kenya, Nakuru Provincial General Hospital, and provides lessons for care of a large number of burned patients in a resource-limited setting. Methods: Data were obtained from retrospective review from hospital registers and patient files. Results: Treatment was provided for 89 victims. Eighty-six (97%) were men; median age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…45 patients died within 1 week and had a total body surface area burned of 80 % as compared with 28 % for survivors. They concluded that in areas where referral to tertiary centers is not possible, district hospitals should have mass disaster plans that involve burn related victims [ 5 ]. In this study, we were able to detail the burn related injuries following the natural disaster SSHS.…”
Section: Discussionmentioning
confidence: 99%
“…45 patients died within 1 week and had a total body surface area burned of 80 % as compared with 28 % for survivors. They concluded that in areas where referral to tertiary centers is not possible, district hospitals should have mass disaster plans that involve burn related victims [ 5 ]. In this study, we were able to detail the burn related injuries following the natural disaster SSHS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, areas with extraordinary burn burden and frequent burn disasters, like sub-Saharan Africa and South Asia, require special attention. (10, 12, 19, 20) Given the high incidence and prevalence of burn injury and complications in LMICs, allocating resources essential for burn care is important for effective humanitarian assistance.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of burns in mass casualty events and terrorist attacks provides an additional source of knowledge on the manifestation and distribution of blast-related burn injuries in settings ranging from Europe (Turégano-Fuentes et al, 2008) and the Middle East (Paydar et al, 2012) to Africa (Van Kooij et al, 2011) and South Asia (Tekade et al, 2017;Yu et al, 2016). For example, Paydar and colleagues, 2012, wrote an overview of the events of a mosque bombing in Shiraz, Iran, outlining the average age of patients (26 years), sex breakdown (67 percent male and 23 percent female), and most-prevalent causes of hospital admission).…”
Section: Prevalence and Characteristics Of Burn Injuries From Mass Ca...mentioning
confidence: 99%